Comparative treatment approach for Sarcoptes and Psoroptes mite infestation in a Boer cross - Marimuthu, Murugaiyah; Abdullah, Faez Firdaus Jesse; Mohammed, Konto; Adamu, Lawan; Tijjani, Abdulnasir; Abba, Yusuf; Sadiq, Muhammad Abubakar; Leow, Yuan Ting; Saharee, Abdul Aziz; Haron, Abdul Wahid (Bangladesh Agricultural University, Faculty of Veterinary Science, 2015)
This case was carried out to compare the healing process and time for the treatment of mange in goats using a combination of Ivermectin with dexamethasone to the earlier Ivermectin with antihistaminics approach. A 3 ½ years old female Boer cross goat was presented with a complaint of crusty lesions on different parts of the body during a routine farm visit in Selangor, Malaysia. Microscopic examinations of the skin scrapes taken revealed Sarcoptes and Psoroptes sp. of mites, while hematological analysis showed slight leucocytosis, neutrophilia with left shift, monocytosis, hyperproteinemia and hyperglobulinemia. Ivermectin injection at 0.2 mg/kg subcutaneously was administered once every 2 weeks in 4 divided doses, while Dexamethasone injection at 1 mg/10 kg and multivitamin at 10 mg/kg IM for 5 days repeated at alternate weeks. Significant improvement was recorded 6 weeks after commencement of treatment and full recovery at 10 weeks. The current drug regimen proved more effective when compared with previous cases that were treated with a combination of ivermectin and antihistaminics.